Are the PHQ-9 and GAD-7 Suitable for Use in India? A Psychometric Analysis - De Man, Jeroen; Absetz, Pilvikki; Sathish, Thirunavukkarasu; Desloge, Allissa; Haregu, Tilahun; Oldenburg, Brian; Johnson, Leslie C. M.; Thankappan, Kavumpurathu Raman; Williams, Emily D. (Frontiers in Psychology, 2021)
Background Cross-cultural evidence on the factorial structure and invariance of the PHQ-9 and the GAD-7 is lacking for South Asia. Recommendations on the use of unit-weighted scores of these scales (the sum of items’ scores) are not well-founded. This study aims to address these contextual and methodological gaps using data from a rural Indian population. Methods The study surveyed 1209 participants of the Kerala Diabetes Prevention Program aged 30-60 years (n at risk of diabetes = 1007 and n with diabetes = 202). 1007 participants were surveyed over 2 years using the PHQ-9 and the GAD-7. Bifactor-(S – 1) modeling and multigroup confirmatory factor analysis were used. Results Factor analysis supported the existence of a somatic and cognitive/affective subcomponent for both scales, but less explicitly for the GAD-7. Hierarchical omega values were .72 for the PHQ-9 and .76 for the GAD-7. Both scales showed full scalar invariance and full or partial residual invariance across age, gender, education, status of diabetes and over time. Effect sizes between categories measured by unit-weighted scores versus latent means followed a similar trend but were systematically higher for the latent means. For both disorders, female gender and lower education were associated with higher symptom severity scores, which corresponds with regional and global trends. Conclusions For both scales, psychometric properties were comparable to studies in western settings. Distinct clinical profiles (somatic-cognitive) were supported for depression, and to a lesser extent for anxiety. Unit-weighted scores of the full scales should be used with caution, while scoring subscales is not recommended. The stability of these scales supports their use and allows for meaningful comparison across tested subgroups. Trial registration Australia and New Zealand Clinical Trials Registry: ACTRN12611000262909 http://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=336603&isReview=true